The last ranger : a novel [large type] - Heller, Peter, 1959- (Random House Large Print, 2023)
"Officer Ren Hopper is a ranger with the National Park Service, tasked with duties both mundane and thrilling: breaking up campgrounds, saving clueless tourists from moose attacks, and attempting to broker an uneasy peace between the wealthy vacationers who tromp through the park with cameras and the residents of hardscrabble Cooke City who want to carve out a meaningful living. When Ren, hiking through the backcountry on his day off, encounters a big man with a dog and a gun chasing a small black bear up a hill, his hackles are raised. But what begins as an investigation into the background of a local poacher soon opens into something far murkier: a shattered windshield, a series of red ribbons tied to traps, the discovery of a frightening conspiracy, and a story of heroism gone awry."--Page 4 of cover.